2016
DOI: 10.21873/anticanres.11083
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Serum Biomarkers (GastroPanel®) in Non-invasive Diagnosis of Atrophic Gastritis. Systematic Review and Meta-analysis

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 44 publications
6
100
0
6
Order By: Relevance
“…To our knowledge, this is the first systematic review with meta‐analysis to assess the performance of the serum panel test for the diagnosis of atrophic gastritis regardless of the site, using (1) a comprehensive literature search, (2) the Updated Sydney System classification of gastritis as reference standard, (3) an appropriate tool for the evaluation of the methodological quality of studies and (4) a multilevel statistical approach for meta‐analysis. A recent meta‐analysis by Syrjanen reported the performance of the panel test “GastroPanel” (Biohit, Finland) for the diagnosis of antrum atrophic gastritis and corpus atrophic gastritis, separately, but not the accuracy of the test regardless of the site of atrophic gastritis . This meta‐analysis included studies that used different histological classifications of atrophic gastritis as reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first systematic review with meta‐analysis to assess the performance of the serum panel test for the diagnosis of atrophic gastritis regardless of the site, using (1) a comprehensive literature search, (2) the Updated Sydney System classification of gastritis as reference standard, (3) an appropriate tool for the evaluation of the methodological quality of studies and (4) a multilevel statistical approach for meta‐analysis. A recent meta‐analysis by Syrjanen reported the performance of the panel test “GastroPanel” (Biohit, Finland) for the diagnosis of antrum atrophic gastritis and corpus atrophic gastritis, separately, but not the accuracy of the test regardless of the site of atrophic gastritis . This meta‐analysis included studies that used different histological classifications of atrophic gastritis as reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…A swallowable ‘cytosponge’ attached to a thread, from which cells are analysed following retrieval, has a 79.9% sensitivity in detecting Barrett’s oesophagus and is capable of detecting a variety of other oesophageal diseases 35 36. A panel of serological biomarkers of gastric atrophy (pepsinogen I and II and amidated G-17) and H. pylori IgG antibodies identifies gastric atrophy of the corpus and antrum with sensitivities and specificities of 70.2% and 51.6% and 93.9% and 84.1%, respectively 37. Gastric capsule endoscopy involves the use of a modified small bowel capsule, adapted to allow visualisation of the upper GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…None of them took clopidogrel or warfarin, and underwent to upper GI endoscopy with biopsy: histopathology confirmed that all patients having serological values according to OGA had OGA (two having OLGA III and one having OLGA IV staging); iii) 10 patients had serological values according to antral gastritis, nine of them with atrophy, that do not influence gastric secretion. 6,10 Twenty-one out of 25 patients (84.0%) had serological values according to H. pylori infection (IgG against H. pylori >30 EIU). Due to the age of our population, no further investigation on current H. pyloristatus were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Although endoscopic findings may be predictive of gastric acid secretion status, non-invasive tool as the determination of serological levels of pepsinogens and gastrin 17 maybe more useful. 6 Gastropanel ® (BIOHIT Oyj, Helsinki, Finland), a combination of G-17 (gastrin-17), PG-I (pepsinogen-I), PG-II (pepsinogen-II) and Helicobacter pylori antibodies of IgG class, has been proposed as a simple non-invasive serological test to select patients with a high risk of harboring AG, who deserve endoscopic examination. 7 This method can effectively describe MAO, since has been already shown that PGI levels significantly correlate with MAO.…”
Section: Introductionmentioning
confidence: 99%